Development of a fast, single-pass, micron-resolution beam position monitor signal processor: Beam test results from ATF2 - Apsimon, R; Bett, D; Burrows, P; Christian, G; Constance, B; Dabiri Khah, H; Perry, C; Resta Lopez, J; Swinson, C (2010)
We present the design of a stripline beam position monitor (BPM) signal processor with low latency (c. 10ns) and micron-level spatial resolution in single-pass mode. Such a BPM processor has applications in singlepass beamlines such as those at linear colliders and FELs. The processor was deployed and tested at the Accelerator Test Facility (ATF2) extraction line at KEK, Japan. We report the beam test results and processor performance, including response, linearity, spatial resolution and latency.